Diagnosis and Management of Refeeding Syndrome - Auliangi Tamayo; Roza Mulyana; Rose Dinda Martini (HM Publisher, 2022)
Refeeding syndrome (RFS) is described as a syndrome of electrolyte abnormalities and changes in body fluids with metabolic abnormalities in malnourished patients who receive refeeding either orally, enteral, or parenterally. Patients at risk for RFS are patients who have lost 10% of their previous body weight in the last 3-6 months, cancer patients who are on chemotherapy, geriatric patients with malnutrition, and patients with anorexia. Clinical manifestations are caused by electrolyte changes that affect neurons, heart and muscle disorders with various symptoms, and even death. The specific characteristics of RFS are the presence of hypophosphatemia and accompanied by other symptoms of electrolyte imbalance such as changes in sodium levels, changes in glucose, protein, fat metabolism, vitamin B1 deficiency, hypokalemia, and hypomagnesemia. The principle of management of RFS is to correct biochemical abnormalities and electrolyte and fluid imbalances. Preventive steps that can be taken are identifying individuals at risk for RFS, monitoring refeeding and administering an appropriate diet regimen.